Study of HIV Resistance Mutations Against Antiretrovirals using Bioinformatics Tools - Peixoto, Roca Tárcio; Nogueira, Lima F. S.; de Oliveira, Santos A.; Souza, Vieira Deusilene; Felipo, Botelho-Souza Luan (Current HIV Research, 2019)
Background: Antiretroviral drugs to HIV-1 (ARV) are divided into classes: Nucleotide Reverse Transcriptase Inhibitors (NRTIs); Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTIs); Protease Inhibitors (PIs); Integrase Inhibitors (INIs); fusion inhibitors and entry Inhibitors. The occurrence of mutations developing resistance to antiretroviral drugs used in HIV treatment take place in a considerable proportion and has accumulated over its long period of therapy. Objective: This study aimed to identify resistance mutations to antiretrovirals used in the treatment of HIV-1 in strains isolated from Brazilian territory deposited at Genbank, as well as to relate to the clinical significance and mechanism of action. Methods: Elucidation of these mutations was by comparative method of peptide sequence resulting from genes encoding therapeutic targets in HIV antiretroviral therapy (ART) of the strains with a reference sequence through bioinformatic genetic information manipulation techniques. Results: Of the 399 sequences analyzed, 121 (30.3%) had some type of mutations associated with resistance to some class of antiretroviral drug. Resistance to NNRTIs was the most prevalent, detected in 77 (63.6%) of the 121 mutated sequences, compared to NRTIs and PIs, whose resistance was detected in 60 (49.6%) and 21 (17.3%), respectively, and to INIs, only 1 (0.8%) sample showed associated resistance mutation. Conclusion: Resistance to HIV ARV was detected at a considerable rate of 30.3%, showing some concerns about the percentage of viral strains that escape the established therapeutic regimen and that circulate currently in Brazil. The non-use of NNRTIs in Brazil is justified by the emergence of resistance mutations. The low prevalence of mutations against INIs is because drugs in this class have a high genetic barrier.
Keywords: mutation